2018
DOI: 10.1515/phys-2018-0135
|View full text |Cite
|
Sign up to set email alerts
|

Fast recognition algorithm for static traffic sign information

Abstract: Aiming at the low recognition rate, low recognition efficiency, poor anti-interference and high missing detection rate of current traffic sign recognition methods, a fast recognition algorithm based on SURF for static traffic sign information of highway is proposed. The expansion of the digital morphological method is used to connect the cracks in the traffic sign. Traffic sign images are corroded according to the corrosion, and the connected areas are contracted or refined. Regions of interest are detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Liu [ 40 ] analyzed the relationship between the information quantity of urban roadside traffic signs and drivers’ visibility based on information transmission. Guo [ 41 ] proposed a fast recognition algorithm based on speeded-up robust features (SURF) for static traffic sign information of highways. Lyu [ 42 ] revealed that the workload is highly related to the amount of information on traffic signs, and reaction time increases with the information grade while driving experience and gender are not significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu [ 40 ] analyzed the relationship between the information quantity of urban roadside traffic signs and drivers’ visibility based on information transmission. Guo [ 41 ] proposed a fast recognition algorithm based on speeded-up robust features (SURF) for static traffic sign information of highways. Lyu [ 42 ] revealed that the workload is highly related to the amount of information on traffic signs, and reaction time increases with the information grade while driving experience and gender are not significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Color space has also been used, for example, in segmentation in HSV [4]. Researchers extracted SURF feature points from signs and used corroding images to match them [5]. In some studies, more complex feature descriptors, such as coarse localization of signs based on the Hough transform [6], were used for sign extraction.…”
Section: Introductionmentioning
confidence: 99%